Peculiarities of Teaching Biology in Universities under Conditions of Digitalization (Journal of Educational Sciences, 2022)
Currently, all areas of society are moving toward the mass use of information systems and technologies. Many countries are introducing information systems into the educational process. Every modernteacher should be fluent in information technology. In this way, it helps to increase student motivationfor the class. Changing the system of relations between the teacher and the student, the content, thestructure of their activities, they affect their motivational emotional environment. The use of informationand technological means allows you to turn the biology lesson into a fascinating and productive lesson.The article considers effective methods of using electronic educational resources and capabilities ofeducational platforms in the conditions of transition to distance learning in accordance with the requirements of the state program “Digital Kazakhstan”. It is emphasized that when teaching students, it is important to use effective modern methods and techniques, as well as visual and auditory elements insteadof methods and approaches that make students dependent on the textbook and limit them to what theteacher teaches. The effectiveness of using videos in biology classes was studied. Student performanceresults are given on the research paper. In particular, the use of video materials during classes allowsstudents to convey the necessary information as accurately as possible, and students, due to their modern capabilities and features, better absorb the material in this way. The results of questionnaires fromdifferent regions on the effectiveness of videos were discussed and analyzed. Thus, the study revealedthe necessity of using videos in biology lessons to facilitate students’ learning and their effectiveness inthe learning process.Key words: information technology, methods, videos, experimental, control, performance,creativity.